ANALYSIS OF THE APPLICATION OF CONCURRENT MANAGEMENT ON EMPLOYEE PERFORMANCE AT PT KARYA ANUGERAH MEDIKA TANGERANG DISTRICT, BANTEN - Shofanisa Alifia Zahra; Chasan Ma'ruf (Journal Of Applied Multidisiplinary Studies, 2024)
This study aims to analyze the effect of concurrent management on employee performance at PT Karya Anugrah Medika, Tangerang Regency, Banten. The main focus of this research is to understand how concurrent management can affect the quality level of employee performance and identify the factors that influence the effectiveness of such management. The research method used is qualitative with a descriptive approach, involving interviews, observation, and documentation as the main data collection techniques. The results showed that concurrent positions have a positive impact in terms of skill development, income generation, network development, and work flexibility. However, there are also some negative impacts such as stress, burnout, conflict of interest, and challenges in achieving work-life balance. Factors that influence the effectiveness of concurrent management include motivation, job satisfaction, and company support. The findings provide insights for companies in optimizing the implementation of concurrent positions to effectively improve employee performance.